Premature Deindustrialization in Indonesia: An Analysis of Spatial Spillover and its Impact on the Regional Economic Convergence - Wandira, Dina; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2026)
This study analyzes the relationship between premature deindustrialization and economic convergence among Indonesian provinces using a spatial approach. It addresses a gap in the literature regarding the neglect of spatial dimensions in the linkage between manufacturing decline and regional inequality. The objectives are to identify the characteristics of deindustrialization, measure spatial spillover patterns, and assess its impact on economic convergence. Employing a Spatial Durbin Model on cross-sectional data from 38 provinces covering the period 2002 and 2024, the findings indicate that deindustrialization is heterogeneous and localized, exhibiting limited spatial clustering patterns. Estimation results reveal that deindustrialization exerts a significant negative direct effect on economic growth, while spatial spillover effects are not consistently identified. Economic convergence persists, as evidenced by a significant negative coefficient on initial income, yet neither deindustrialization nor its spatial spillovers are empirically proven to impede this convergence. In conclusion, deindustrialization in Indonesia represents a fragmented regional structural phenomenon with weak spatial connectivity, while convergence is predominantly determined by region-specific internal factors. Policy implications emphasize the need for industrial corridor development and strengthening interprovincial production linkages to spatially transmit industrialization.